Application of Learning Media and Technology in Schools to Increase Student Interest in Learning - Puhka, Prakash; Annemari, Barreiro; Harry, Rannikko (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
Long before the development of technology, in the world of education the learning media used has not developed rapidly. Educators are required to increase student interest in learning by using modern technology media. Learning media is a technology that carries messages that can be used for learning purposes and is a communication to convey subject matter. Learning technology is utilization, management to facilitate the learning process. The purpose of this study is to determine the application of learning media and technology that can increase student interest in learning, especially in schools. This research uses Quantitative research by conducting online surveys and in-depth interviews with school teachers. The results of this study explain that there are several applications that are used as media for learning, one of which is YouTube. The conclusion of this study explains that there are many technologies or applications that can be utilized to increase student interest in learning. The limitation of this research is that researchers only collect information related to applications that can be utilized to increase student interest in learning, researchers hope that future researchers can develop learning media applications as a tool to help teachers and students in the learning and teaching process